2019
DOI: 10.1111/ocr.12282
|View full text |Cite
|
Sign up to set email alerts
|

Osteocytes and mechanical loading: The Wnt connection

Abstract: Structured Abstract Bone adapts to the mechanical forces that it experiences. Orthodontic tooth movement harnesses the cell‐ and tissue‐level properties of mechanotransduction to achieve alignment and reorganization of the dentition. However, the mechanisms of action that permit bone resorption and formation in response to loads placed on the teeth are incompletely elucidated, though several mechanisms have been identified. Wnt/Lrp5 signalling in osteocytes is a key pathway that modulates bone tissue's respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 21 publications
0
17
0
Order By: Relevance
“…Wnt signaling plays a vital role in skeletal health, mainly via osteogenic differentiation of precursor cells, osteocyte viability, and osteocyte signaling to other bone cells ( 43 , 44 ). Wnt/β-catenin activation in osteocytes mainly contributes to the anabolic effect in bone ( 45 ).…”
Section: Introductionmentioning
confidence: 99%
“…Wnt signaling plays a vital role in skeletal health, mainly via osteogenic differentiation of precursor cells, osteocyte viability, and osteocyte signaling to other bone cells ( 43 , 44 ). Wnt/β-catenin activation in osteocytes mainly contributes to the anabolic effect in bone ( 45 ).…”
Section: Introductionmentioning
confidence: 99%
“…Wnt/β-catenin signaling response to mechanical loading is critical for bone homeostasis [21,45], and it is also reported to promote osteogenesis and inhibit adipogenesis [46]. Wnt/β-catenin signaling is a primary fate regulator of adipocytes and osteoblasts, whereby an accumulation of β-catenin was associated with a dose-dependent increase in osteogenesis and a decrease in adipocyte differentiation [47].…”
Section: Discussionmentioning
confidence: 99%
“…[ 36 , 37 ] Recent evidence has indicated that modulation of sclerostin levels, via activation of the Piezo1-Akt pathway and inhibition of Wnt/LRP5 and TSC1/mTORC1 signaling, appears to finely tune the regional and local osteogenesis coordinated by osteocytes in response to increased mechanical stimulation. [ 11 14 , 38 ] In addition, the expression of sclerostin increased when mechanical loading decreased and reduced when mechanical loading increased [Figure 2 ]. [ 38 40 ] Therefore, sclerostin modulation seems to be a target to develop the effect of orthodontic treatment.…”
Section: Sclerostin In Tooth Movementmentioning
confidence: 99%
“…[ 8 10 ] This suggests that the loss of sclerostin has a positive impact in periodontitis progression. Meanwhile, current research has shown that the expression of sclerostin is influenced by mechanical force stimulation [ 11 14 ] ; thus, sometimes, periodontitis can be induced during orthodontic treatment. [ 15 ] Further, orthodontic tooth movement has been demonstrated as biological bone remodeling induced by mechanical force.…”
Section: Introductionmentioning
confidence: 99%